PELATIHAN MIKROTIK BERBASIS MODEL PROBLEM BASED LEARNING DI SMKS RIYADLUL QURAN NGAJUM KABUPATEN MALANG - Khoirudin Asfani; Hakkun Elmunsyah; Hary Suswanto; Wahyu Nur Hidayat; Febrianto Alqodri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract Computer and Network Engineering is one of the Vocational High School expertise programs engaged in the field of Information and Technology. The facilities needed to support learning activities for Computer and Network Engineering are also relatively cheaper among other informatics majors, so that Computer and Network Engineering expertise programs are very favorite and are widely opened in Vocational High School that have ICT fields, especially in the Malang area. However, the problems currently being faced are competition for jobs in the Network Engineer field and the incompatibility of graduate competencies with the type of work obtained. Riyadlul Quran Vocational School, Ngajum, Malang, is one of the B-accredited Islamic boarding Vocational Schools that has educational potential and graduates in the field of Computer and Network Engineering. Based on the results of interviews and observations with teachers at schools, around 10% of graduates work in their respective fields, 20% continue their studies at the higher education level, and the rest work outside their fields of expertise. The decline in the quality of student learning outcomes at the Riyadlul Quran Vocational High School is suspected to be the result of the ongoing Covid 19 pandemic and the lack of learning innovations carried out by teachers. This service activity targets the realization of a better quality of learning through learning methods that can be done both online and offline. Improving the quality of learning is carried out through training for teachers of Riyadlul Quran Vocational High School. Through these training activities, it is hoped that it can provide new ideas in teaching (pedagogy) and increase ability/competence (professional) in the field of Mikrotik-based computer networks for Computer and Network Engineering teachers at Riyadlul Quran Vocational School. Service activities are carried out and begin with 1) initial observations, 2) problem formulation based on the results of initial observations, 3) needs analysis, 4) development and 5) testing, 6) training activities and 7) evaluation, and 8) reporting and 9) finalization of Community Service outputs. The training approach method used is guided training and mentoring, both offline and scheduled online. It is hoped that through this service activity, teachers are able to implement computer network practice learning methods using Mikrotik which can be done online or offline, as well as provide an overview in carrying out future learning innovations independently. In addition, this activity can also be a reference for other vocational schools that have similar problems. Abstrak Teknik Komputer dan Jaringan (TKJ) merupakan salah satu program keahlian Sekolah Menengah Kejuruan (SMK) yang bergerak di bidang Informasi dan Teknologi. Fasilitas yang diperlukan untuk menunjang kegiatan pembelajaran bagi TKJ juga tergolong lebih murah diantara jurusan informatik lainnya, sehingga program keahlian TKJ menjadi sangat favorit dan banyak dibuka di SMK yang memiliki bidang TIK, khususnya di daerah Malang Raya. Namun, permasalahan yang saat ini dihadapi adalah persaingan untuk mendapatkan pekerjaan di bidang Network Engineer dan tidak sesuainya kompetensi lulusan dengan jenis pekerjaan yang didapatkan. SMK Riyadlul Quran, Ngajum, Kabupaten Malang, merupakan salah satu SMK Swasta berbasis pesantren terakreditasi B yang memiliki potensi pendidikan dan lulusannya di bidang TKJ. Berdasarkan hasil wawancara dan observasi bersama guru di sekolah, sekitar 10% lulusan bekerja sesuai dengan bidangnya, 20% melanjutkan studi di jenjang pendidikan tinggi, dan sisanya bekerja di luar bidang keahlian. Penurunan kualitas hasil belajar siswa di SMK Riyadlul Quran ditengarai akibat dari pandemi Covid 19 yang tidak kunjung selesai dan inovasi pembelajaran yang dilakukan guru juga tergolong kurang. Kegiatan pengabdian ini menargetkan terwujudnya kualitas pembelajaran yang lebih baik melalui metode pembelajaran yang dapat dilakukan baik secara daring maupun luring. Peningkatan kualitas pembelajaran dilakukan melalui pelatihan kepada guru SMK Riyadlul Quran. Melalui kegiatan pelatihan tersebut, diharapkan dapat memberikan ide baru dalam mengajar (pedagogi) dan peningkatan kemampuan/kompetensi (profesional) di bidang jaringan komputer berbasis mikrotik bagi guru TKJ di SMK Riyadlul Quran. Kegiatan pengabdian dilakukan dan diawali dengan 1) observasi awal bersama mitra, 2) perumusan masalah berdasarkan hasil observasi awal, 3) analisis kebutuhan, 4) pengembangan modul dan 5) uji coba, 6) kegiatan pelatihan dan 7) evaluasi, serta 8) pelaporan dan 9) finalisasi luaran PKM. Metode pendekatan pelatihan yang dilakukan adalah pelatihan terbimbing dan pendampingan, baik secara luring maupun secara daring terjadwal. Diharapkan, melalui kegiatan pengabdian ini guru mampu mengimplementasikan metode pembelajaran praktik jaringan komputer menggunakan Mikrotik yang dapat dilakukan secara daring maupun luring, serta memberikan gambaran dalam melakukan inovasi pembelajaran kedepannya secara mandiri. Selain itu, kegiatan ini juga dapat menjadi referensi pada SMK-SMK lainnya yang mengalami permasalahan serupa.